Chitosan and Titanium Dioxide Are More Effective in Improving Seed Yield and Quality in Nanoparticle Compared to Non-Structured Form: A Case Study in Five Milk Thistle Ecotypes (Silybum marianum (L.) Gaertn.) - Jafari, Samira; Mousavi-Fard, Sadegh; Rezaei Nejad, Abdolhossein; Mumivand, Hasan; Sorkheh, Karim; Nikoloudakis, Nikolaos; Fanourakis, Dimitrios (My University, 2022)
Milk thistle is an important medicinal crop. In this two-year field study, the optimal form [bulk (non-structured), nanoparticles (NPs)] and concentration (0, 50, 100 mg L−1) of chitosan and titanium dioxide (TiO2) applications for improving seed yield, as well as seed mineral (N, Mg, Fe, Ti), protein, and oil contents were investigated in five ecotypes. Leaf gas exchange, ratio of variable to maximum fluorescence (Fv/Fm), and hydration were also evaluated in situ. Chitosan and TiO2 improved all traits under study, with the former generally being more effective. When applied in the NP form, the positive effect was stronger. For chitosan NPs, a low concentration was optimal. Increased hydration status was associated with enhanced stomatal conductance, which, together with Fv/Fm, were positively related to photosynthetic rate. The seed yield per plant was positively related to main capitulum traits (i.e., diameter, number, and weight of seeds), as well as to seed weight and number of capitula per plant. In conclusion, the improvement of seed yield and quality by application of chitosan and TiO2 in either form was underlain by the same components, though their relative importance depends on the ecotype. Chitosan NPs were most effective, demonstrating an economical, eco-friendly, and sustainable means to stimulate milk thistle yield.